1996
DOI: 10.2166/wst.1996.0554
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage on kinetic selection to control aerobic filamentous bulking

Abstract: In various activated sludge systems, sludge grows under transient (unbalanced) conditions and storage of internal polymers becomes important. Differences in storage capacity under transients are often used to explain kinetic control of bulking, but storage is neither studied in detail nor usually included in modelling. For this reason, the transient response of different aerobic mixed cultures was studied by experimentally determining the role of storage. Two different mixed cultures (bulking and non-bulking) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 0 publications
0
38
0
2
Order By: Relevance
“…It has been shown that the configuration of the system (i.e., plug flow vs. completely mixed) has a large impact on kinetics, which will ultimately determine the size of the selector. Furthermore, storage is an intrinsic bacterial ecophysiological process that plays a key role in selector-like systems (Majone et al, 1996;Martins et al, 2003a;2003b;van Loosdrecht et al, 1997), and can influence both stoichiometry and kinetics.…”
Section: Kinetic and Storage Aspects Related To Anoxic And Anaerobic mentioning
confidence: 99%
“…It has been shown that the configuration of the system (i.e., plug flow vs. completely mixed) has a large impact on kinetics, which will ultimately determine the size of the selector. Furthermore, storage is an intrinsic bacterial ecophysiological process that plays a key role in selector-like systems (Majone et al, 1996;Martins et al, 2003a;2003b;van Loosdrecht et al, 1997), and can influence both stoichiometry and kinetics.…”
Section: Kinetic and Storage Aspects Related To Anoxic And Anaerobic mentioning
confidence: 99%
“…Enhanced PHA storage was found in activated sludge systems subjected to alternate carbon substrate availability, also designated as feast and famine (FF) (Majone et al, 1996;van Loosdrecht et al, 1997). Under FF, microorganisms that can rapidly store the substrate have a competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is less emphasis on the extracellular hydrolysis of complex organic matter because a significant part of the ''slow oxygen uptake rate'' is due to growth on stored substrate (Gujer et al, 2000), whereas in ASM1, this is solely due to growth on hydrolyzed substrate. Experiments indicate, however that the extent of storage and the level of internal hydrolysis depend much on the parameters of system operation and feast (presence of external substrate) and famine (absence of external substrate) conditions created within the system (Majone et al, 1996). Recent modeling efforts attempt to bring clarification to simultaneous substrate storage and growth (Beun et al, 2000;Karahan-Gül et al, 2003;Krishna and van Loosdrecht, 1999).…”
Section: Introductionmentioning
confidence: 99%